SPORT IN POLITICAL LIFE OF MODERN RUSSIAN SOCIETY: YOUTH COMPONENT - A. M. Chilieva; L. A. Keleman (Современная наука и инновации)
Author's study of the role of sport in the political life of modern Russian society is presented taking into account the youth factor and the relationship of all components of the political process.